Intertwined World: Economic Networks, Positionality and Growth - Tenzin Tamang (Review of Economic and Business Studies, 2020)
Deepening globalisation and the unrestricted flow of resources across domestic borders has led to the emergence of an intertwined world, which has replaced the influence of local to global forces on places. In this situation, there has been an advent of a network paradigm, as understanding how nations are placed within these networks has become critical in ‘globalizing’ policies. Although literature posits that the fate of places has become increasingly reliant to their position in networks shaped by the international flows of investment and trade, this is more often asserted than demonstrated, as little studies probes on whether positionality of nations in a network directly converts to improved economic performance. Drawing upon data on Foreign Direct Investments (FDI) from financial times, in this paper we test the relationship between network positionality in different scales of integration and economic performance between 2003 and 2016 for the Southeast Asian countries.